THE TRANSCULTURATION OF CHINESE AND AMERICAN CULTURE IN THE MOVIE “KUNG FU PANDA 2008” = Sự hội tụ văn hóa Trung – Mỹ trong bộ phim “Kung Fu Panda 2008” - Vũ, Diệu Linh (2020)
The agreeableness of movie in general and Kung Fu Panda movie in particular in cultural perspective is the main inspiration of this research. This study is aimed at the realization of transculturation reflected in the movie “Kung Fu Panda 2008” and the implication of the usefulness of movie in understanding Cross-Cultural Communication. To satisfy these research objectives, several instruments, are utilized effectively by the author. This study employs qualitative method with the two main instruments. Movie analysis and observation are likely to be recognized as the most notable instrument which assists the author to reach majority of research objectives. It is explored in the study that the movie “Kung Fu Panda 2008” displays clearly the transculturation presented in the literature review, namely, Chinese characterizations and American patterns, and the flexibility of Chinese and American culture in the movie. Besides, the author expects to recommend the helpfulness of using movie in the study of Cross-Culture Communication.